Molecular Recognition of a Thomsen–Friedenreich Antigen Mimetic Targeting Human Galectin‐3. (11th September 2018) - Santarsia, Sabrina; Grosso, Ana Sofia; Trovão, Filipa; Jiménez‐Barbero, Jesús; Carvalho, Ana Luísa; Nativi, Cristina; Marcelo, Filipa
Abstract: Overexpression of the Thomsen–Friedenreich (TF) antigen in cell membrane proteins occurs in 90 % of adenocarcinomas. Additionally, the binding of the TF antigen to human galectin‐3 (Gal‐3), also frequently overexpressed in malignancy, promotes cancer progression and metastasis. In this context, structures that interfere with this specific interaction have the potential to prevent cancer metastasis. A multidisciplinary approach combining the optimized synthesis of a TF antigen mimetic with NMR, X‐ray crystallography methods, and isothermal titration calorimetry assays was used to unravel the molecular structural details that govern the Gal‐3/TF mimetic interaction. The TF mimetic has a binding affinity for Gal‐3 similar to that of the TF natural antigen and retains the binding epitope and bioactive conformation observed for the native antigen. Furthermore, from a thermodynamic perspective, a decrease in the enthalpic contribution was observed for the Gal‐3/TF mimetic complex; however, this behavior is compensated by a favorable gain in entropy. From a structural perspective, these results establish our TF mimetic as a scaffold to design multivalent solutions to potentially interfere with Gal‐3 aberrant interactions and for likely use in hampering Gal‐3‐mediated cancer cell adhesion and metastasis. Abstract : Carbohydrate blockers : The Thomsen–Friedenreich (TF) antigen and galectin‐3 (Gal‐3) are both overexpressed in cancer. Herein we report the structural features that govern the interaction between a TF mimetic and Gal‐3. Our mimetic conserves the binding epitope, the bioactive conformation, and retains a binding affinity similar to that of the natural TF antigen.